Aspekty prawne przyrodniczego wykorzystania osadów ściekowych = Legal aspects of the sewage sludge natural use - Sadecka, Zofia; Myszograj, Sylwia; Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Development of sewage sludge is one of the most important problems of the national waste management. Natural use of sewage sludge in Poland (next to the landfill) is currently the simplest and cheapest way to their final disposal. The article presents the general principles of sludge development and the possibility of practical application it on the example of waste water treatment plant on PE = 2600.
Keywords: osady ściekowe; przyrodnicze wykorzystanie; prawo; sewage sludge; natural utilization; legal